Green Synthesis of Carbon Nanospheres for Enhanced Electrochemical Sensing of Dopamine. Issue 6 (26th January 2023) - Lei, Peng; Zhou, Ying; Sun, Xincheng; Dong, Chuan; He, Yinghe; Liu, Yang; Shuang, Shaomin
Abstract: The detection of dopamine (DA) has received enormous attention since it is widely recognized as an important neurotransmitter associated with nerve signaling and some diseases. In this work, glucose‐derived carbon nanospheres (CNs) are synthesized by the green hydrothermal approach and are served to modify electrodes for the detection of DA. The CNs were successfully synthesized and were investigated in detail by various characterization technologies. The CNs modified glassy carbon electrode (CNs/GCE) exhibits better electrochemical sensing performance with a wide linear range of 0.05–1600 μM and a low limit of 8.3 nM for determination of DA, as compared with the modified electrodes reported previously. The CNs/GCE was successfully applied to detect DA in human serum samples, which makes it promising for a variety of biomedical applications. More importantly, this work shows a novel green and simple strategy for the development of cost‐effective and high‐performance sensing materials, which provides more opportunities for design of electrochemical sensors with future capabilities of mass production in practical applications. Abstract : Sweet nanospheres : Glucose‐derived carbon nanospheres (CNs) synthesized by a simple hydrothermal approach were employed for electrochemical determination of dopamine. The CNs‐modified glassy carbon electrode exhibits excellent sensing performance and satisfactory results when applied in human serum samples, making it promising for biomedical applications.